(untitled) (Context: Journal of Interdisciplinary Studies, 2022)
This article explores various questions about a poem written by Antun Ivanošić (1740–1800), a priest and poet from Slavonia, in which he glorifies the Habsburg victory over “the Turks” during the Dubica War (1788–1791). The author twice mentinos Mustafa Gaibija (Muṣṭafā Ghāʼibī or Ghaybī), a 17th century Muslim scholar, mystic and poet. Gaibija holds an important place in the sacral history of the Banja Luka region and of the Bosnian Muslims in general. His memory is also preserved in the folk traditions of the Catholics of Slavonia. The references to Gaibija in Ivanošić’s poem have previously passed unnoticed both in both Bosnian historiography and Croatian literary studies. This article highlights the significance of these references and thus contributes to a better understanding of Christian-Muslim relations on the borders of empires and to the representation of Muslims among the Southern Slavs of the 18th century.